2007
DOI: 10.1111/j.1439-0426.2006.00831.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology ofPseudocorynopoma doriai(Pisces: Characidae) in the High Basin of the Samborombón River, province of Buenos Aires, Argentina

Abstract: The reproductive period of the Glandulocaudine Pseudocorynopoma doriai was determined by the analysis of 240 females, 90 males and 138 immature individuals collected monthly in the Manantiales and the El Portugue´s rivers. The reproductive period is seasonal, occurring from late winter to mid-summer, with another reproductive peak of smaller magnitude in early autumn. The mean monthly GSI in males has a significant correlation with rainfall. Other analyzed environmental variables, including temperature, photop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Other inseminating species of the Stevardiinae [ Gephyrocharax atracaudatus (Meek & Hildebrand 1912), Corynopoma riisei Gill 1858 and Pseudocorynopoma doriae Perugia 1891] also reproduce during colder months or have unseasonal and extended reproductive periods (Kramer, ; Winemiller, ; Menni & Almirón, ; Ferriz et al ., ). A possible advantage of this reproductive strategy is that the females are always ready to spawn when the environmental conditions become beneficial for the offspring, and in the absence of males (Burns et al ., ; Azevedo et al ., ; Burns & Weitzman, ).…”
Section: Discussionmentioning
confidence: 97%
“…Other inseminating species of the Stevardiinae [ Gephyrocharax atracaudatus (Meek & Hildebrand 1912), Corynopoma riisei Gill 1858 and Pseudocorynopoma doriae Perugia 1891] also reproduce during colder months or have unseasonal and extended reproductive periods (Kramer, ; Winemiller, ; Menni & Almirón, ; Ferriz et al ., ). A possible advantage of this reproductive strategy is that the females are always ready to spawn when the environmental conditions become beneficial for the offspring, and in the absence of males (Burns et al ., ; Azevedo et al ., ; Burns & Weitzman, ).…”
Section: Discussionmentioning
confidence: 97%
“…Kamrani et al (2010) observed predominance of males over females in the blue swimmer crab, Portunus pelagicus. However, the predominance of females was reported in catfish, Liposarcus multiradiatus (Liang et al, 2005), Pseudocorynopoma doriai (Ferriz et al, 2007), Acetes indicus (Amin et al, 2009), Liza abu (Chelemal et al, 2009), Rasbora tawarensis (Muchlisin et al, 2010), Mystus tengara (Gupta and Banerjee, 2013). The sex ratio can also differ from one population of the same species to another, and may also vary year to year (Gupta and Gupta, 2006;Wang et al, 2003).…”
Section: Fecunditymentioning
confidence: 99%
“…In serial spawners, yolked oocytes are repeatedly recruited from unyolked oocytes over the spawning season (DeVlaming, 1983), therefore, a longer spawning period will result in more batches of spawned eggs compared to a shorter spawning period. Additionally, given the positive correlation between fecundity and fish size (Ferriz et al., 2007), a larger fish with greater gonad volume is expected to make a greater contribution to population egg production than its smaller counterpart. The result of such variability in egg production may result in the capacity for variations in population growth.…”
Section: Introductionmentioning
confidence: 99%